Crystal structure of bis(5-amino-1,2,4-triazol-4-ium-3-yl)methane sulfate, C5H10N8O4S - Zhang Guo-Tao; Wang Hua; Li Hong-Ya; Yan Biao (Zeitschrift für Kristallographie - New Crystal Structures)
C5H10N8O4S, Orthorhombic, Pba2 (no. 32), a = 7.7320(11) Å, b = 12.8686(19) Å, c = 5.0657(8) Å, β = 90°, V = 504.04(13) Å3, Z = 2, R gt(F) = 0.0298, wR ref(F 2) = 0.0748, T = 296(2) K.